Intestinal injury and the gut microbiota in patients with Plasmodium falciparum malaria - Sriboonvorakul, N; Chotivanich, K; Silachamroon, U; Phumratanaprapin, W; Adams, JH; Dondorp, AM; Leopold, SJ (Public Library of Science, 2023)
The pathophysiology of severe falciparum malaria involves a complex interaction between the host, parasite, and gut microbes. In this review, we focus on understanding parasite-induced intestinal injury and changes in the human intestinal microbiota composition in patients with Plasmodium falciparum malaria. During the blood stage of P. falciparum infection, infected red blood cells adhere to the vascular endothelium, leading to widespread microcirculatory obstruction in critical tissues, including the splanchnic vasculature. This process may cause intestinal injury and gut leakage. Epidemiological studies indicate higher rates of concurrent bacteraemia in severe malaria cases. Furthermore, severe malaria patients exhibit alterations in the composition and diversity of the intestinal microbiota, although the exact contribution to pathophysiology remains unclear. Mouse studies have demonstrated that the gut microbiota composition can impact susceptibility to Plasmodium infections. In patients with severe malaria, the microbiota shows an enrichment of pathobionts, including pathogens that are known to cause concomitant bloodstream infections. Microbial metabolites have also been detected in the plasma of severe malaria patients, potentially contributing to metabolic acidosis and other clinical complications. However, establishing causal relationships requires intervention studies targeting the gut microbiota.